Filogenia de Catopsis Griseb. (Bromeliaceae, Tillandsioideae) - Martínez Correa, Nancy (Universidad Autónoma Metropolitana, 2019)
Catopsis comprises epiphytic and rupiculous herbs distributed throughout Mexico, Central America, the Caribbean, and northern South America. The genus is more diverse in Mexico, where more than 85 % of its species inhabit. Catopsis is characterized by its seeds with an appendage formed by numerous hairs at the chalaza. Most species are dioecious although others are monoecious and trioecious. In this paper are presented a taxonomic treatment, one phylogenetic hypothesis obtained with morphological and molecular data, and one proposal on the evolution of sexual systems present in the genus. This work was based on the revision of 2 388 herbarium specimens from 37 herbaria, corresponding to 2 257 collections, as well as in the collection of live plants and chloroplast DNA sequences (rps16 and matK). Catopsis comprises 26 species and one variety, five of which are described here as new to science. Catopsis compacta, C. occulta, C. paniculata, C. pendula, C. wawranea and Catopsis sp. 5 are endemic to Mexico, whereas C. pisiformis is endemic to Panama and C. werckleana is known only from Costa Rica. In the taxonomic treatment, the nomenclature is clarified, as well as the typification of the genus, to each species the acepted name and synonym are included, as well as a description, wich is completed with data related to morphology, phenology and geographic distribution. A key to identify the species is provided. The phylogenetic hypotheses obtained suggest that Catopsis is monophyletic, but it is not possible recognize subgenera. Evolutionary patterns are observed within the species related to the number of leaves in the rosette, the shape of the foliar blade, the shape and length of the peduncle bracts, the shape of primary bracts, and the shape of the petals. Of all species, 22.22 % are monoecious, 55.55 % are dioecious, and 18.15 % are trioecious. The hypothesis of the evolution of sexual systems suggests that dioecy is the plesiomorphic character and that both trioecy and monoecy are evolutionary novelties for Catopsis. ; El género Catopsis incluye plantas epífitas y/o rupícolas y su distribución comprende México, Centroamérica, el Caribe y la parte norte de Sudamérica, siendo más diverso en México, en donde habitan más de 85 % de sus especies. Catopsis se caracteriza por el apéndice de sus semillas, formado por numerosos tricomas que nacen de la calaza. La mayoría de las especies son dioicas y otras son monoicas o trioicas. En este trabajo se presentan el tratamiento taxonómico del género, una hipótesis filogenética obtenida tanto con datos morfológicos como moleculares y una hipótesis relativa a la posible evolución de los sistemas sexuales presentes en el género. Este trabajo se basó en la revisión de 2 388 ejemplares de herbario, provenientes de 37 herbarios, correspondientes a 2 257 números de colecta, así como en recolecciones propias de plantas vivas y en secuencias de ADN de cloroplasto (rps16 y matK). Catopsis comprende 26 especies y una variedad, seis de las cuales se proponen como nuevas para la ciencia. Catopsis compacta, C. occulta, C. paniculata, C. pendula, C. wawranea y Catopsis sp. 5 son endémicas de México, mientras que C. pisiformis es endémica de Panamá y C. werckleana se conoce únicamente de Costa Rica. En el tratamiento taxonómico se aclaran diversos aspectos nomenclaturales, así como la tipificación del género, para cada especie se incluyen el nombre aceptado y la sinonimia, así como una descripción, lo que se completa con datos relativos a la morfología, a la fenología y a la distribución geográfica de cada una de ellas. También se proporciona una clave para identificar a las especies. La hipótesis filogenética obtenida sugiere que el género Catopsis es monofilético, sin embargo, no es posible reconocer subgéneros. Se observan patrones evolutivos dentro de las especies relacionados con el número de hojas en la roseta, forma de la lámina foliar, forma y longitud de las brácteas del pedúnculo, forma de las brácteas primarias y forma de los pétalos. Del total de especies, 22.22 % son monoicas monoclinas, 55.55 % son dioicas y 18.15 % son trioicas. La hipótesis de la evolución de los sistemas sexuales sugiere que la dioecia es el carácter plesiomórfico y que tanto la trioecia como la monoecia son novedades evolutivas para Catopsis.